DIABETES DURATION AND RETINAL NERVE FIBER LAYER THICKNESS RELATED DEGREE OF DIABETIC RETINOPATHY: Oral Presentation - Observational Study - Resident - Delfi; Nadia, Felanda Ahsanu; Sari, Masitha Dewi (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesDiabetic retinopathy is an ocular complication of diabetes mellitus (DM). Several studies have shownthat neurodegenerative changes in the retina occur earlier than microvascular changes.Measurement of retinal nerve fiber layer thickness can detect neurodegeneration at an early stage.This study aims to analyze the relationship of diabetes duration and retinal nerve fiber layerthickness with degree of diabetic retinopathy in type 2 diabetes mellitus patients. MethodsThis research was analytic observational research with cross-sectional design. The sample was type2 diabetes mellitus patients with diabetic retinopathy who visited the eye clinic at the University ofSumatera Utara General Hospital. The sample were then analyzed with the Kruskal Wallis test tofind relationship of diabetes duration and retinal nerve fiber layer thickness with degree of diabeticretinopathy in type 2 diabetes mellitus patients. ResultsThe sample of this study were 20 subjects with diabetic retinopathy and 20 subjects without diabeticretinopathy as the control group. The mean duration of having DM in the group of patients with mildNPDR was 5.33 years, with moderate NPDR was 9.13 years and with PDR was 15.33 years. Usingthe Kruskal Wallis test revealed that there was no significant relationship between degree ofdiabetic retinopathy with Avg RNFL (p=0.495), superior RNFL (p=0.385), inferior RNFL (p=0.111),temporal RNFL (p=0.064), nasal RNFL (p=0.535). ConclusionThere was a significant difference between diabetes duration with degree of diabetic retinopathy butno significant between retinal nerve fiber layer thickness with degree of diabetic retinopathy.